The effects of different breeding systems on egg productivity and egg quality characteristics of rock partridges - Ozbey, O.; Esen, F. (Elsevier, 2007)
This study was carried out to investigate the effects of different breeding systems (breeding on the ground and in the cage) on the egg production and egg characteristics of Rock Partridges. Egg production values of the ground and cage system groups were determined as 41.30 and 49.40%, respectively, and this difference was found to be significant (P < 0.05). The weight values of the eggs were 23.86 g in the ground system and 22.08 g in the cage system (P < 0.05). The difference between the shape index values, which were determined as 75.39 in the ground system and as 77.65 in the cage system, was statistically significant (P < 0.05). In addition, the values for yolk index (48.42 and 44.11), albumen index (1.45 and 1.66), Haugh unit (83.24 and 86.78), shell weight (2.39 and 2.86), yolk weight (8.55 and 7.89), and albumen weight (12.46 and 11.78) obtained in the ground and cage system, respectively, were obtained to be statistically different (P < 0.05). It was observed that the Rock Partridges could be bred in ground and cage systems during the egg production period, and although the investment cost and equipment expenditure increase in cage breeding, the egg quality, shape index, albumen index, and Haugh unit of Rock Partridges decrease dramatically in ground breeding.
Keywords: Rock Partridge; breeding system; egg productivity; egg quality